PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS HIERARKI KONSEP PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN - Dinantia, Ariyessa; Amran, Elva Yasmi; ', Rini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This Research aims to develop Student Activities Worksheets Based on Hierarchy of Concept on the Solubility and Solubility Product subject valid based on the feasibility aspect of content, language, serve and graphic. The type of this research is research and development (R and D) with reference to the development process of 4-D model. The subject of this research is student activities worksheets based on hierarchy of concept. Instrument of data collection are validation given to four validators, and from analysis data obtained by the validity of aspect of content, aspect of language, aspect of serve, and aspect of graphic are 91,87%, 93,75%, 95,31%, and 92,19% with valid category. Student activities worksheets which validated by the validators tested to 30 students and get response result with percentage of 87,54% with positive category. Based on the result of data analysis can be concluded that student activities worksheets based on hierarchy of concept that produced is valid and can be used for the subject solubility and solubility product.Keywords: Solubility and Solubility Product, Hierarchy of Concept, Student ActivitiesWorksheet